Peer educator training program for enhancing knowledge on issues in the growth and development of adolescents and risk behavior problems in Indonesian context - Susanto Tantut; Rahmawati lis; Wantiyah (Sciendo, 2018)
This article aimed to evaluate the effects of an educational intervention programme on improving peer educator (PE) knowledge in issues around growth and development and its risk behavior problems of adolescents in Indonesia.